Low-dose CT angiography of the lower extremities: a comparison study of image quality and radiation dose. Issue 2 (February 2021) - Park, S.; Park, S.H.; Hwang, J.H.; Kim, J.H.; Lee, K.H.; Park, S.H.; Shin, J.H.; Pak, S.Y.; Kang, J.M.
Abstract : AIM: To investigate the image quality and radiation dose of ultralow-dose (ULD) and low-dose (LD) lower-extremity computed tomography (CT) angiography (LE-CTA) using the advanced modelled iterative reconstruction (ADMIRE) algorithm to detect peripheral arterial disease (PAD) in comparison with standard-dose (SD) CT. MATERIALS AND METHODS: One hundred and seven consecutive patients were examined using LE-CTA at 70 kVp and a dual-source scanner to achieve three image sets using 30% (ULD), 70% (LD), and 100% (SD) tube loads. Qualitative analysis was conducted by examining the three image sets for overall quality. The image quality of arterial segments was analysed by two independent readers. In addition, the CT dose index (CTDIvol ) was measured in the three image sets. RESULTS: The mean overall quality scores were 3.4±0.6 for ULD CT, 3.9±0.3 for LD CT, and 3.9±0.2 for SD CT. Both readers scored the arterial segments as 2–4 (adequate–excellent) in the three image sets. In addition, 89.4% (93/104) and 54.8% (57/104) segments of PAD with calcified plaques were scored 4 between SD and LD CT and between SD and ULD CT, respectively, and 45.2% (47/104) segments had a lower score by one point in ULD CT compared with SD CT. The mean CTDIvol was 4.1±1.1 mGy for SD CT, 2.9±0.8 mGy for LD CT, and 1.2±0.3 mGy for ULD CT. CONCLUSIONS: LD/ULD CT at 70 kVp using ADMIRE reconstruction enables a reduction in the radiation dose while enabling adequate evaluation or follow-up of PAD based on LE-CTA. Highlights: Peripheral arterial disease may expose patients to repeated CT examinations. The radiation exposure should be minimized for evaluation and follow-up. Low-dose CT angiography provides similar image quality to the standard-dose CT. The image quality is maintained by applying model-based iterative reconstruction. Low-dose CT angiography enables dose reduction and preserves diagnostic quality.